1998
DOI: 10.1094/cchem.1998.75.4.455
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Fusarium Scab in Wheat Using Machine Vision and a Neural Network

Abstract: A neural network was used to relate color and texture features of wheat samples to damage caused by Fusarium scab infection. A total of 55 color and texture features were extracted from images captured by a machine vision system. Random errors were reduced by using average values of features from multiple images of individual samples. A four‐layer backpropagation neural network was used. The percentage of visual scabby kernels (%VSK) estimated by the trained network followed the actual percentage with a correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 4 publications
0
27
0
1
Order By: Relevance
“…Sapirstein (1995) reviewed the literature on image analysis of grain through the mid 1990s. Detection of diseased kernels by image analysis is a relatively recent endeavor, with some published works on corn (Ng et al, 1998) and wheat (Ruan et al, 1998;Luo et al, 1999) available. In Ruan's study, neural networks were used on color and textural features of bulk samples to develop a model for wheat scab detection.…”
mentioning
confidence: 99%
“…Sapirstein (1995) reviewed the literature on image analysis of grain through the mid 1990s. Detection of diseased kernels by image analysis is a relatively recent endeavor, with some published works on corn (Ng et al, 1998) and wheat (Ruan et al, 1998;Luo et al, 1999) available. In Ruan's study, neural networks were used on color and textural features of bulk samples to develop a model for wheat scab detection.…”
mentioning
confidence: 99%
“…The review of recent research works has demonstrated the advancements and progress of various content based remote sensing images retrieval systems in the recent past, however state-of-the-art works [24] [26] [27] focus mainly on semantic based image retrieval concepts, especially in remote sensing archive [26] [27]. Despite lot of problems have been addressed in the literature [25], developing a wellstructured intelligent feature extraction methods are considered to be the most complex challenge that prevails in the current system.…”
Section: The Problem Statementmentioning
confidence: 99%
“…The relationship between colour and texture features of wheat samples to scab infection rate was studied using a neural network method [63]. It was found that the infection rates estimated by the system followed the actual ones with a correlation coefficient of 0.97 with human panel assessment and maximum and mean absolute errors of 5 and 2%, respectively.…”
Section: Wheatmentioning
confidence: 99%